Systematic Review of Usability Factors, Models, and Frameworks with Blockchain Integration for Secure Mobile Health (mHealth) Applications: SLR: Usability standards and models for mHealth Applications - Feroz, Irum; Ahmad, Nadeem (Blockchain in Healthcare Today, 2024)
This systematic review examines critical usability factors that influence the adoption of mobile health (mHealth) applications among older adults and identifies gaps in current usability models, including ISO 9241-11, Nielsen’s heuristics, and PACMAD. This review also explores the potential role of blockchain technology in enhancing multimodal medical data systems within mHealth applications. A comprehensive search across six databases yielded 1,073 studies, with 60 meeting inclusion criteria. Studies were analyzed through thematic synthesis to identify key success factors (RQ1) and comparative analysis to assess limitations in existing frameworks (RQ2). Key factors promoting mHealth adoption included ease of use, efficiency, error prevention, learnability, memorability, and user satisfaction. Blockchain integration emerged as a promising approach to improve data security, interoperability, and user trust, particularly for older adults who engage with complex, multimodal health data. Findings from RQ2 highlighted gaps in usability models, such as the lack of age-specific guidance for multimodal interaction, error recovery, and data privacy. These results underscore the need to define a new usability framework and incorporate blockchain to meet the unique needs of older adults in mHealth applications, supporting both secure and accessible healthcare management.